1972
DOI: 10.1029/jb077i026p04966
|View full text |Cite
|
Sign up to set email alerts
|

Magmatism and tectonic settings

Abstract: Mutual relationships of mobile lithospheric plates define two distinct tectonic environments each characterized by diagnostic magmatism. A compressional environment occurs at loci of plate convergence; quartz‐ and hypersthene‐normative intermediate, acid and basic members of the calc‐alkaline orogenic suite are emplaced above a dipping seismic zone. A tensional environment occurs mainly at loci of plate divergence, areas characterized by networks of deep fractures, offset by transform faults. Products of nonor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(24 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…Elevated Ti02 is often associated with "nonorogenic" basalts (e.g., Chayes, 1964;Martin and Piwinskii, 1972). However, Glazner and Richardson (1983) showed that Ti02 cannot be used to discriminate syn-and post-subduction basalts in western North America.…”
Section: Notesmentioning
confidence: 97%
“…Elevated Ti02 is often associated with "nonorogenic" basalts (e.g., Chayes, 1964;Martin and Piwinskii, 1972). However, Glazner and Richardson (1983) showed that Ti02 cannot be used to discriminate syn-and post-subduction basalts in western North America.…”
Section: Notesmentioning
confidence: 97%
“…In general, rock suites emplaced during an anorogenic event are higher in Si02 and P2O5, higher in alkalies (especially K), low in CaO, AI2O3 and MgO, and show definite iron enrichment when compared to orogenic rock associations (Martin and Piwinskii, 1972). Also, in anorogenic suites few rocks have Si02 contents that are less than 65% (Rogers and Greenberg, 1981).…”
Section: Anorogenic Nature Of the Rock Suites And Summarymentioning
confidence: 99%
“…In this context, it is worth noting the well-established association of a bimodal (and, typically, alkalic) plutonic-volcanic suite with anorogenic (extensional) environments; orogenic (compressional) environments, on the other hand, are associated with calcalkaline suites showing a spectrum of compositions (Martin and Piwinskii, 1972). This bimodality, for example, constitutes the major basis for interpreting the Silurian-Devonian Maine coastal volcanic belt as having formed under conditions of crustal extension (Gates and Moench, 1981).…”
Section: Plate Tectonic Modelsmentioning
confidence: 99%